2010
DOI: 10.1021/bi1014425
|View full text |Cite
|
Sign up to set email alerts
|

Bombyx Adipokinetic Hormone Receptor Activates Extracellular Signal-Regulated Kinase 1 and 2 via G Protein-Dependent PKA and PKC but β-Arrestin-Independent Pathways

Abstract: Neuropeptides of the adipokinetic hormone (AKH) family are among the best studied hormone peptides. They play important roles in insect hemolymph sugar homeostasis, larval lipolysis, and storage-fat mobilization. Mechanistic investigations have shown that, upon AKH stimulation, adipokinetic hormone receptor (AKHR) couples to a Gs protein and enhances adenylate cyclase activity, leading to intracellular cAMP accumulation. However, the underlying molecular mechanism by which this signaling pathway connects to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…The influx of extracellular Ca 2ϩ via G q -mediated phospholipase C is also essential for the adipokinetic effect (36,37). Our previous studies have demonstrated that agonist-activated AKHRs signal the ERK1/2 pathway via PKA-and calcium-involved PKC-dependent pathways (18). We have further demonstrated that AKHRs are rapidly internalized in a dose-and time-dependent manner via the clathrin-coated pit pathway upon agonist stimulation, and internalized receptors were slowly recovered to the cell surface after the removal of AKH peptides (26).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The influx of extracellular Ca 2ϩ via G q -mediated phospholipase C is also essential for the adipokinetic effect (36,37). Our previous studies have demonstrated that agonist-activated AKHRs signal the ERK1/2 pathway via PKA-and calcium-involved PKC-dependent pathways (18). We have further demonstrated that AKHRs are rapidly internalized in a dose-and time-dependent manner via the clathrin-coated pit pathway upon agonist stimulation, and internalized receptors were slowly recovered to the cell surface after the removal of AKH peptides (26).…”
Section: Discussionmentioning
confidence: 72%
“…In addition, AKH activates phospholipase C to induce the release of Ca 2ϩ from intracellular Ca 2ϩ stores (16,17). Our previous studies have demonstrated that AKH stimulation not only led to a ligand concentration-dependent mobilization of intracellular Ca 2ϩ and cAMP accumulation but also elicited PKA and PKC pathway-mediated transient activation of the extracellular signal-regulated kinase 1 and 2 (ERK1/2) pathways in HEK293 cells stably expressing AKHR (18). We have further demonstrated that AKH2 exhibits comparable activities in intracellular cAMP accumulation to AKH1, but Bombyx AKH3 was much less effective in activating Bombyx AKHR, strongly implying that there is more likely other intrinsic AKHRs that exist as a high affinity receptor for AKH3 in Bombyx (19).…”
mentioning
confidence: 99%
“…The mouse neural crest-derived cell line, Neuro-2a, and Human Embryonic Kidney 293 cells, HEK-293, were used as described previously [23]. Dulbecco's modified Eagle's medium (DMEM) and fetal bovine serum (FBS) were purchased from Gibco (Carlsbad, CA).…”
Section: Reagentsmentioning
confidence: 99%
“…MTNR1A (in pFLAG-CMV-3) and β-arrestin 2 (in pEGFP-N1) was a kind gift of Zhou Naiming (Zhejiang University, China) [23]. MTNR1A was modified by PCR and subcloned into EGFP, ECFP, or mCherry.…”
Section: Plasmid Construction and Transfectionmentioning
confidence: 99%
“…The Drosophila AKHR was the first to be cloned and was deorphanized by making use of the electrophysiological assay (Park et al, 2002), and its characterization was confirmed by Staubli et al (2002) using a bioluminescence assay. Later, AKHRs were also identified and characterized in other insect species: Periplaneta americana (Hansen et al, 2006; Wicher et al, 2006a), A. gambiae (Belmont et al, 2006), B. mori (Staubli et al, 2002; Zhu et al, 2009; Huang et al, 2010), and T. castaneum (Li, unpublished data). Two putative AKHR variants have been predicted in A. aegypti (Kaufmann et al, 2009) and one AKHR is identified in the Apis genome (Hauser et al, 2006).…”
Section: Deorphanized Neuropeptide Receptorsmentioning
confidence: 99%